Biomechanical comparison of all-polyethylene total knee replacement and its metal-backed equivalent on periprosthetic tibia using the finite element method - Apostolopoulos, Vasileios; Boháč, Petr; Marcián, Petr; Nachtnebl, Luboš; Mahdal, Michal; Pazourek, Lukáš; Tomáš, Tomáš (Journal of orthopaedic surgery and research, 2024)
BACKGROUND: Total knee arthroplasty (TKA) with all-polyethylene tibial (APT) components has shown comparable survivorship and clinical outcomes to that with metal-backed tibial (MBT). Although MBT is more frequently implanted, APT equivalents are considered a low-cost variant for elderly patients. A biomechanical analysis was assumed to be suitable to compare the response of the periprosthetic tibia after implantation of TKA NexGen APT and MBT equivalent. METHODS: A standardised load model was used representing the highest load achieved during level walking. The geometry and material models were created using computed tomography data. In the analysis, a material model was created that represents a patient with osteopenia. RESULTS: The equivalent strain distribution in the models of cancellous bone with an APT component showed values above 1000 με in the area below the medial tibial section, with MBT component were primarily localised in the stem tip area. For APT variants, the microstrain values in more than 80% of the volume were in the range from 300 to 1500 με, MBT only in less than 64% of the volume. CONCLUSION: The effect of APT implantation on the periprosthetic tibia was shown as equal or even superior to that of MBT despite maximum strain values occurring in different locations. On the basis of the strain distribution, the state of the bone tissue was analysed to determine whether bone tissue remodelling or remodelling would occur. Following clinical validation, outcomes could eventually modify the implant selection criteria and lead to more frequent implantation of APT components.
Keywords: polyethylen; analýza metodou konečných prvků; Finite Element Analysis; protézy kolene; protézy - design; Tibia; Knee Prosthesis; kovy; totální endoprotéza kolene; lidé; Aged; Polyethylene; Prosthesis Design; Arthroplasty, Replacement, Knee; Metals; Humans; tibie; senioři